Water Bodies Area Extraction from Resourcesat-2 Awifs Image Using Automated Algorithm, Visakhapatnam District, Andhra Pradesh, India - M. Ganesh, K; A.R.K.Raju, P; Gopalakrishna Murthy, N; Srinivasu, N (International Journal of Engineering and Technology, 2018)
Irrigation water was supplied to supplement the water available from rainfall, So the purpose of crop production of application of water to soil is the Irrigation.Â Due to lack of amount and timing of rainfall, to the moisture requirement of crops and irrigation, It is necessary to meet the needs of food and fibbers, So the raise crops is essentialÂ in many area of the world.Â Water features composed of all surface water features viz. reservoirs, tanks & ponds, beels, oxbow lakes, derelict water and brackish water, which are the function of intensity of rainfall, rainfall amounts etc. over season/a year.Â The mapping, monitoring of dynamics of surface water bodies were acquire by satellite sensors through synoptic and dynamic coverage of earth surface at frequent intervals.Â In FCC water bodies appear as different hues depending on their physical characteristics such as depth of water (bottom reflection), turbidity, etc. Water appears dark due to which absorbs all infrared radiations.Â This helps in easy contrast distinction between water and land in near-infrared band.Â Mapping, monitoring and inventory of water features over wide areas by Satellite data is a reputed proficiency for creation of dynamic databases.Â Our present area of interest includes an automatic approach to capture the water body from a Resourcesat-2 AWiFS (Advanced Wide-Field Sensor) imagery using a Automated Algorithm for extraction of surface water bodies model.Â The dynamics of surface water bodies in study on geospatial analysis of the evaluation of water feature sheets for the month of April, 2018 of the study area.Â The water features information was generated on geospatial database from the Resourcesat-2 AWiFS imageÂ by using bands of 1.55- 1.70 Âµm (SWIR), 0.77-0.86 Âµm (NIR), 0.62-0.68 Âµm (Red) and 0.52-0.59 Âµm (Green) for the estimation of the water spread area.Â The Water Spread Area (WSA) calculated for each is 11304 ha [1] and [2].Â Â